1978
DOI: 10.1136/thx.33.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Results of treating primary tumours of the trachea by irradiation.

Abstract: . (1978). Thorax, 33,[387][388][389][390][391][392][393]. Results of treating primary tumours of the trachea by irradiation. Forty-four patients presented with primary tumours of the trachea over a 25-year period. Thirty-nine of them were treated by irradiation. Of these, 24 (61-5%) died as a result of their disease while 30% are either alive and well (4-4-11 years) or have died of intercurrent disease (average four years). Recurrences or metastases when they occurred were in the first two years after diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 5 publications
0
21
0
1
Order By: Relevance
“…Fields et al [7] reported that 6 of 7 patients attained a complete response and ultimate local control with a radiation dose of 60 Gy or greater, compared with 1 of 11 patients with a radiation dose of less than 60 Gy. Better response rates with doses of 60 Gy or higher have also been reported in other studies [8,16,20,21]. However, the improvements in control rates have been achieved with a concomitant increase in the incidence of complications, the most common being tracheal stenosis requiring dilatation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Fields et al [7] reported that 6 of 7 patients attained a complete response and ultimate local control with a radiation dose of 60 Gy or greater, compared with 1 of 11 patients with a radiation dose of less than 60 Gy. Better response rates with doses of 60 Gy or higher have also been reported in other studies [8,16,20,21]. However, the improvements in control rates have been achieved with a concomitant increase in the incidence of complications, the most common being tracheal stenosis requiring dilatation.…”
Section: Discussionmentioning
confidence: 67%
“…However, the improvements in control rates have been achieved with a concomitant increase in the incidence of complications, the most common being tracheal stenosis requiring dilatation. Esophageal strictures, tracheo-esophageal fistulae and arterial rupture have also been reported [7,8,20].…”
Section: Discussionmentioning
confidence: 99%
“…''Radiation bronchitis'', manifesting itself as a reddened hyperaemic airway mucosa and thickened bronchial secretions, following therapeutic external-beam radiation doses (50-60 Gy) applied to the lung has seldom been described. However, only a few articles have reported stenosis in proximal bronchi 6-15 months after external-beam radiation for lung cancer using 80 Gy doses [6], or tracheal stenosis after irradiation of tracheal cancers with doses ranging 50-70 Gy [7,8]. No extrinsic compressions were noted.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cancer of the trachea is extremely rare (1); accounting for 0.1-0.4% of all newly diagnosed airway cancers, or 2.6 new cases per 1,000,000 people per year (2,3). In tracheal carcinogenesis, malignant transformation may be idiopathic or due to carcinogen exposure, immunosuppressant use, radiation or smoking (4,5).…”
Section: Introductionmentioning
confidence: 99%